Identification and functional analysis of Wall-Associated Kinase genes in Nicotiana tabacum - Li, Ling; Cao, Linggai; Li, Jintao; Zhang, Zhiqiang; Liu, Jie; Ren, Zhongying; Zhang, Jie; Wang, Rengang; Miao, Yangfan; Yu, Shizhou; Li, Wei (Frontiers in Plant Science, 2025)
IntroductionWall-associated kinases (WAKs) are pivotal in linking plant cell walls to intracellular signaling networks, thereby playing essential roles in plant growth, development, and stress responses. MethodsThe bioinformatics analysis was employed to identify WAK genes in tobacco. The expression levels of NtWAK genes were assessed by qRT-PCR. The subcellular localization of WAK proteins was observed in tobacco cells and Arabidopsis protoplasts. Kinase activity of the WAK proteins was evaluated through in vitro assays. ResultsWe conducted a comprehensive genome-wide identification and analysis of the WAK gene family in tobacco (Nicotiana tabacum). A total of 44 WAK genes were identified in the tobacco genome, which were further classified into three distinct groups. Phylogenetic analysis comparing tobacco WAKs (NtWAKs) with Arabidopsis WAKs (AtWAKs) revealed species-specific expansion of these genes. The WAK proteins within each group displayed similar gene structures and conserved motif distributions. Promoter region analysis indicated that cis-elements of NtWAK genes are primarily involved in regulating plant growth and development, phytohormone signaling, and stress responses. Expression profiling under NaCl, PEG, and ABA treatments suggested that certain NtWAK genes may play key roles in modulating responses to abiotic stress. Three-dimensional structural predictions and subcellular localization analysis showed that NtWAK proteins from the three subgroups exhibit high cytoplasmic similarity and are primarily located to the plasma membrane. Kinase activity assay confirmed that they possess phosphorylation activity. DiscussionThis study represents the first genome-wide analysis of the WAK gene family in N. tabacum, laying the groundwork for future functional investigations.